Hell and back again [videorecording (DVD)] - Dennis, Danfung; Dennis, Danfung; Harris, Nathan. Sgt (Docurama Films : Distributed by New Video, 2011)
From his embed with US Marines Echo Company in Afghanistan, photojournalist and filmmaker Danfung Dennis reveals the devastating impact a Taliban machine-gun bullet has on the life of 25-year-old Sergeant Nathan Harris. The film seamlessly transitions from stunning war reportage to an intimate portrait of one man's personal struggle at home in North Carolina, where Harris confronts the physical and emotional difficulties of re-adjusting to civilian life with the love and support of his wife.